2017
DOI: 10.1080/03007995.2017.1391757
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes involved in vasoactive eicosanoid synthesis affect cardiovascular risk in renal transplant recipients

Abstract: Our results show, for the first time to our knowledge, that two SNPs in CYP2C8 and CYP2J2, which synthesize EETs, may modify CV outcomes in renal transplant recipients, a population that is already at a high risk of suffering these events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…Given the major role of EETs in sustained flow-mediated dilatation [21][22][23] , the reduced EET production in response to the increase in blood flow may promote endothelial dysfunction of conduit arteries in kidney transplant recipients. This mechanism may contribute to the deleterious impact of LoF CYP450 SNPs on cardiovascular outcomes in this population 41 . Furthermore, patients carrying R287Q had a higher magnitude of flow-mediated dilatation but also of endothelium-independent dilatation to GTN.…”
Section: Discussionmentioning
confidence: 95%
“…Given the major role of EETs in sustained flow-mediated dilatation [21][22][23] , the reduced EET production in response to the increase in blood flow may promote endothelial dysfunction of conduit arteries in kidney transplant recipients. This mechanism may contribute to the deleterious impact of LoF CYP450 SNPs on cardiovascular outcomes in this population 41 . Furthermore, patients carrying R287Q had a higher magnitude of flow-mediated dilatation but also of endothelium-independent dilatation to GTN.…”
Section: Discussionmentioning
confidence: 95%
“…There is a growing body of evidence pointing to AA-derived vasoactive eicosanoids as important players in the cardiorenal function (Gervasini et al, 2015[ 13 ][ 14 ], 2018[ 15 ]; Fang et al, 2018[ 10 ]; Imig, 2019[ 22 ]). These findings, together with the existence of preclinical data linking these AA metabolites to the renal damage induced by hyperglycemia (Luo et al, 2009[ 25 ]; Eid et al, 2013[ 9 ]), suggest that the levels of these eicosanoids could be useful indicators of the presence of DKD in renal patients, a hypothesis we test in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping was carried out by real-time PCR using commercial TaqMan ® SNP genotype assays from Thermofisher Scientific (Rockford, Il, USA). These SNPs were selected based on previous reports stating their influence on clinical outcomes [18,[22][23][24][25][26].…”
Section: Genetic Analysismentioning
confidence: 99%
“…In this regard, we have previously shown that the onset of post-transplant diabetes mellitus in renal transplant recipients is dependent on the presence of variants in genes expressed in the kidney that participate in the epoxygenase pathway [15]. In addition, these polymorphisms have also been related to the development of renal injury [16,17], and cardiovascular (CV) disease [18], whose risk is greatly elevated in DKD patients. However, in spite of this background, the influence of genetic polymorphisms in the AA epoxygenase route on DKD remains untested.…”
Section: Introductionmentioning
confidence: 99%